Electrochemical Reduction of CO2 to Alcohols: Current Understanding, Progress, and Challenges. Issue 1 (23rd September 2021) - Wang, Shanwen; Kou, Tianyi; Baker, Sarah E.; Duoss, Eric B.; Li, Yat
Abstract : In comparison with conventional methods, electrochemical CO2 reduction (CO2 RR) represents a promising and environmentally friendly method to generate value‐added products and mitigate anthropogenic climate change. Herein, the recently reported CO2 RR catalysts that show high selectivity and activity toward alcohol production are highlighted. The current understanding of reaction pathways on different catalyst surfaces for alcohol production is highlighted and strategies to enhance CO2 RR catalytic performance are discussed. Finally, the views on the challenges and possible future paths for the field are shared. Abstract : Alcohols are essential precursors and chemical intermediates for many valuable products. Electrochemical CO2 reduction to alcohols is an attractive strategy to alleviate anthropogenic climate change and generate useful products simultaneously. The current understanding of the process, recent progress, and challenges in the field is discussed.